2001
DOI: 10.1159/000048851
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Colitis during Pregnancy and Contraceptive Medication

Abstract: Ischemic bowel disease is generally considered a disease of the elderly and usually consists of reversible colopathy. Nonocclusive causes of ischemic colitis include low-flow states due to cardiac dysfunction and hypovolemia and use of certain medications including progestational medication. We report 2 cases of ischemic colitis in young women. The first one occurred in a young patient who developed three consecutive episodes of ischemic colitis during her pregnancy, whereas the second woman presented with isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Some studies have suggested that a genetic predisposition to thrombosis may play an important role in the pathogenesis of ischemic colitis in young women (5). It has also been described during pregnancy, probably related to the high circulating levels of estrogens (6). In almost half of the cases, the cause is not found (2).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that a genetic predisposition to thrombosis may play an important role in the pathogenesis of ischemic colitis in young women (5). It has also been described during pregnancy, probably related to the high circulating levels of estrogens (6). In almost half of the cases, the cause is not found (2).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, cases of ischemic colitis associated with pregnancy are very rare. 4,5 We report a case of ischemic colitis occurring in the eighth week of pregnancy.…”
Section: A Case Of Ischemic Colitis During Pregnancymentioning
confidence: 99%
“…The presence of ischemic colitis in young patients should always raise the possibility of drug involvement, especially oral contraceptives, 18 cocaine, 19,20 and migraine medication, like ergotamine derivatives 21 and potentially sumatriptan. 22 Oral contraceptives produce a hypercoagulable state and may cause mesenteric vein fibrosis.…”
Section: Ischemic Colitismentioning
confidence: 99%